2019
DOI: 10.3390/catal9030263
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doping in Double Perovskite PrBaCo2(1-x)Fe2xO6-δ: Insights into Structural and Electronic Effects to Enhance Oxygen Evolution Catalyst Stability

Abstract: Perovskite oxides have been gaining attention for its capability to be designed as an ideal electrocatalyst for oxygen evolution reaction (OER). Among promising candidates, the layered double perovskite—PrBaCo2O6-δ (PBC)—has been identified as the most active perovskite electrocatalyst for OER in alkaline media. For a single transition metal oxide catalyst, the addition of Fe enhances its electrocatalytic performance towards OER. To understand the role of Fe, herein, Fe is incorporated in PBC in different rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…The same holds true, to a smaller extent, for Fe ( Figure S4a-c), since the trend in the initial Fe oxidation state is the same but the shifts in the Fe-K edge are smaller compared to those measured for the Co K-edge. This match in these trends has already been observed for BSCF [8][9][10][11][12][13] or non-BSCF perovskite-type oxides [8][9][10]13,39], but this is the first time that it is shown that the initial Co oxidation state in BSCF-and, with that, its OER activity-can be directly tuned by changing synthesis parameters. The reason for this connection between Co oxidation state in BSCF and its OER activity lies in the concentration of oxygen vacancies [8].…”
Section: Tem Images Insupporting
confidence: 73%
“…The same holds true, to a smaller extent, for Fe ( Figure S4a-c), since the trend in the initial Fe oxidation state is the same but the shifts in the Fe-K edge are smaller compared to those measured for the Co K-edge. This match in these trends has already been observed for BSCF [8][9][10][11][12][13] or non-BSCF perovskite-type oxides [8][9][10]13,39], but this is the first time that it is shown that the initial Co oxidation state in BSCF-and, with that, its OER activity-can be directly tuned by changing synthesis parameters. The reason for this connection between Co oxidation state in BSCF and its OER activity lies in the concentration of oxygen vacancies [8].…”
Section: Tem Images Insupporting
confidence: 73%
“…The different oxygen stoichiometries in the PBCO samples have important consequences in the (nominal) cobalt average oxidation state [18] (as shown by the progressive decrease of the average Co oxidation state shown in the Co K‐edge XANES spectra in Figure S4, Supporting Information), which results from a combination of Co 2+ and Co 3+ for δ <0.5 and of Co 3+ and Co 4+ for δ >0.5. It has been shown that the Co oxidation state in the pristine perovskite electrocatalyst, such as Ba 0.5 Sr 0.5 Co 1− x Fe x O 3− δ , La 0.2 Sr 0.8 Co 1− x Fe x O 3− δ and PBCO, [5a, 7b, 19] strongly impacts the OER activity. The Co oxidation state has an influence not only on the local geometry, as detailed in the previous section, but also on the electronic configuration of the cobalt atoms.…”
Section: Resultsmentioning
confidence: 99%
“…[83] Additionally, there are cases where the stabilization of metastable structures and interfaces is linked with the electrochemical environment, as demonstrated for BaTiO3, for which the bare surfaces have been calculated unstable. [84] In the most simple way, computational Pourbaix diagrams can be constructed to estimate the electrochemical stability [85][86][87] and metastability [88] of the solid/liquid(water) interface at the atomistic and bulk level and to design novel materials [89][90][91] . This methodology combines computational (bulk) information on solid phases (total energies) and experimental data for dissolved species (dissolution energies).…”
Section: Modelling Metastability At the Interfacesmentioning
confidence: 99%